2020
DOI: 10.4067/s0034-98872020000200160
|View full text |Cite
|
Sign up to set email alerts
|

Manifestaciones clínicas y anticuerpos asociados y específicos de miositis en 15 pacientes chilenos con dermatomiositis: serie clínica en un centro universitario

Abstract: Clinical manifestations and antibody profile in 15 patients with dermatomyositis Background: Certain associated and specific myositis antibodies are related to certain clinical phenotypes of dermatomyositis (DM), disease severity and the presence of cancer. Aim: To describe the clinical profile of Chilean patients with DM and their associated and specific myositis antibodies. Material and Methods: Review of medical records of 15 patients with DM aged 31 to 72 years. Their clinical characteristics, laboratory t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 31 publications
0
9
0
2
Order By: Relevance
“…Corroborating data from the literature, 10,11,[18][19][20][21][22][23][24][25][26][27] DM mainly affected females. Furthermore, in the present study, there was a predominance of mestizo and White ethnicities.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…Corroborating data from the literature, 10,11,[18][19][20][21][22][23][24][25][26][27] DM mainly affected females. Furthermore, in the present study, there was a predominance of mestizo and White ethnicities.…”
Section: Discussionmentioning
confidence: 78%
“…RP-ILD represents approximately 22% of all cases of ILD in patients with DM, 18,21,[23][24][25] but the prevalence of RP-ILD can reach 75% of all cases of ILD in Asian populations. 10,11 Studies in Latin American centers have observed a prevalence of ILD ranging from 16.5% to 33.3%, 21,26,27 and none of these studies has reported cases of RP-ILD. The most striking feature in the present study is the low frequency of RP-ILD (1.5%); therefore, our study corroborates the few studies available that were conducted with individuals from Latin American countries.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations